A Classification of Object-Oriented Development Methodologies - Capretz, L. F.; Lee, P. A. (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 1992: Anais do VI Simpósio Brasileiro de Engenharia de SoftwareDO - 10.5753/sbes.1992.25179, 1992)
In the last few years, demand for object oriented software systems has increased dramatically, and it is widely accepted that present software engineering methodologies are unable to cope with the needs of that demand. The object oriented paradigm has promised to revolutionize software development: as a result, several methodologies have recently arisen to support software development based on an object oriented approach. This paper is concerned with object oriented methodologies for software systems and proposes a classification scheme for existing object oriented development methodologies. Additionally, the paper presents gaps which could be filled with the development of new object oriented methologies.